Observation on haematological abnormalities in patients with chronic kidney disease (CKD) - Rahman, Md Mahbubur; Dutta, Pradip Kumar; Hoque, Mahmudul; Khan, Md Iftikher Hossain; Dutta, Asok Kumar; Hasan, Mahtab Uddin (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v18i1.3811 Journal of Chittagong Medical College Teachers' Association 2007: 18(1):3-5